Impact of adiposity markers on Peak expiratory flow rate in young adult South Indian females - Jnaneshwara Panduranga Shenoy; J Shivakumar; B Kalpana; Shankar K Bhat (Wolters Kluwer Medknow Publications, 2014)
Background: Even though several factors like respiratory muscle strength, lung compliance, resistance to airflow, and elastic recoil of lungs determine lung functions, physical factors such as height, weight and central pattern of fat distribution also affect the pulmonary functions. Objective: The present study was done to assess the impact of both general as well as central adiposity markers on PEFR in young adult females. Materials and Methods: The study was conducted on 186 healthy young female medical students in the age group of 18-22 years. The study group was divided into three groups based on BMI (as per WHO Asian guidelines). Those with BMI between 18.5 to 22.9 kg/m 2 were considered as normal weight individuals, those having a BMI of 23-24.9 kg/m 2 were taken as overweight individuals and those with a BMI more than 25 were considered as obese. Waist circumference (WC), Waist to hip ratio (WHR) and waist to height ratio were also calculated; these serve as measures for central pattern of fat distribution. PEFR was recorded with Wright's peak flow meter and the best of three readings was considered. The data obtained was statistically analyzed using one way ANOVA and Pearson's correlation tests. A P-value less than 0.05 was considered as significant. Results: Mean value of PEFR did not show significant differences when compared between three groups. On correlation a negative association of various adiposity markers with PEFR was observed and was more related with central adiposity markers than BMI. Conclusion: Our findings suggest that obesity itself and especially the pattern of body fat distribution have independent effects on PEFR in young adult females. Abdominal adiposity may influence pulmonary functions by restricting the descent of the diaphragm and limiting lung expansion as compared to overall adiposity which may compress the chest wall.